ANALISIS KEMAMPUAN 6C (CRITICAL THINKING, CREATIVITY, COLLABORATION, COMMUNICATION, CHARACTER, CITIZEN SHIP) SISWA KELAS V MIN 3 PEKANBRAU - Ruri Darmayani Putri; Zaka Hadikusuma Ramadan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the 6Cs (critical thinking, creativity, collaboration, communication, character, and citizenship) abilities of grade V students at MIN 3 Pekanbaru in the learning process. This research uses a qualitative approach with the type of phenomenological research. The research informants consisted of the head of the madrasah, a class V teacher, and nine students who were selected based on the high, medium, and low ability categories. Data was collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The validity of the data is obtained through source triangulation and triangulation techniques. The results of the study show that the 6C ability of grade V students at MIN 3 Pekanbaru has developed to varying degrees. Critical thinking skills can be seen from students' ability to express opinions accompanied by logical reasons, analyze problems, ask questions, and conclude learning. The ability to be creative is seen through the ability to generate ideas and complete tasks creatively. The ability to collaborate is shown through cooperation, division of tasks, and responsibilities in groups. Communication skills can be seen from the courage to express opinions, ask questions, answer questions, and present the results of discussions. The character aspect is reflected in the attitude of discipline, honesty, responsibility, and care, while the citizenship aspect is shown through compliance with rules, concern for the environment, respect for diversity, and participation in school activities. Overall, students' 6C abilities have developed well, although they still need reinforcement in some aspects